2018
DOI: 10.1055/a-0640-2956
|View full text |Cite
|
Sign up to set email alerts
|

Earlier use of capsule endoscopy in inpatients with melena or severe iron deficiency anemia reduces need for colonoscopy and shortens hospital stay

Abstract: Background and study aims  Capsule endoscopy(CE) is a well-established investigation for iron deficiency anemia (IDA) and melena, usually following negative upper and lower endoscopy. We aimed to study the effect of earlier CE in the investigative pathway for inpatients with IDA or melena at a large tertiary referral centre. Patients and methods  We analyzed inpatients undergoing CE for IDA or melena from 2005 to 2017, without signs/symptoms suggesting lower gastrointestinal tract pathology. Patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…Second, CE is a widespread, well‐tolerated diagnostic tool that perfectly fits with the need for a timely on‐demand SB assessment even in an emergency setting and at the patient's bedside . Notably, the diagnostic yield of enteroscopy decreases substantially with time.…”
Section: Enteroscopy: a Powerful Weapon To Solve Big Problems In The mentioning
confidence: 99%
See 4 more Smart Citations
“…Second, CE is a widespread, well‐tolerated diagnostic tool that perfectly fits with the need for a timely on‐demand SB assessment even in an emergency setting and at the patient's bedside . Notably, the diagnostic yield of enteroscopy decreases substantially with time.…”
Section: Enteroscopy: a Powerful Weapon To Solve Big Problems In The mentioning
confidence: 99%
“…Very recently, three different studies (one prospective from Germany, one retrospective from Scotland, one prospective RCT from the USA) have raised the debate on the early use of CE in non‐hematemesis GI bleeding. Two of them have shown that CE carried out soon after negative upper endoscopy allows for immediate detection of the bleeding site. In the third study, Marya et al .…”
Section: Enteroscopy: a Powerful Weapon To Solve Big Problems In The mentioning
confidence: 99%
See 3 more Smart Citations